PENGARUH KUNJUNGAN WISATAWAN ASING TERHADAP EKONOMI PARIWISATA INDONESIA - Amelia Hutauruk; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research to analyze the Influence of Foreign Tourist Visits on Indonesian Tourism Economy (Case Study: Raja Ampat Tourism Festival), with case studies in Papua. Papua is a tourist destination that has been known to the world. Since then many foreign tourists come to Papua to be able to witness and enjoy the culture, natural beauty and hospitality of Papuans. Papua and tourism can not be separated. It is not only the Papuan government that many hope from the service sector to drive the wheel of development, but most of the people also rely on the sector.The development of the tourism industry in a region can not work without government intervention as a regulator, and the private sector as an investor. The participation of both parties is necessary in order to create an ideal condition for the success of the tourism economy's goals. One of the cornerstones of tourism development secured by the Constitution of the State is to develop tourism should be based on local community empowerment, arts, and (charm) by taking into account the preservation of traditional art and culture as well as the preservation of the local environment. It is proper that the development of tourism is utilized to support the creation of the objectives of the economy.The economic problems facing West Papua are highly vulnerable to external factors. In 2014, the economic growth rate of West Papua grew slower by 5.38 percent compared to the year 2013. Likewise in 2015 which experienced an economic slowdown of 4.10 percent. The sluggish economic condition of West Papua is mainly triggered by the Indonesian economic situation during 2014-2015.In contrast to foreign tourists who have higher income levels than Indonesians, these better financial conditions enable them to enjoy diving as one of Raja Ampat's most popular tourist attractions. The rate of foreign tourist arrivals more than domestic tourists.